SCIENTIFIC VALUES ON THE EUROPEAN LEGAL REGULATION ON THE CONSUMER CREDIT AGREEMENT - Olesea PLOTNIC; Rodica CRUDU (EURINT, 2021)
With the increase of revenue, including in the budget sphere, which stimulates the planning of purchases of products that could improve the quality of life, with the reduction of interest rates by banks, the citizens are increasingly stimulated to conclude credit agreements. The subjects of the civil legal relationship in consumer law must be on the one hand the consumer and on the other hand the professional, the entrepreneur, the creditor. From the essence of the notions, obtained by the common law and Directive 2008/48 / on consumer credit agreements, it follows that the notion of consumer and professional, is notions that includes the legal relationship in the sense of consumer protection law, and the notion of creditor. Through this research paper we propose to analyze the credit agreement both from the perspective of common law and agreement to special rules established by Directive no. 2008/48 and the Law Rep. of Moldova no.202 / 2013 regarding the credit agreement for consumers.